2005 Academy of Management Review Best Article Award (Academy of Management Review, 2006)
This article reveals that the 2005 “Academy of Management Review” Best Article Award went to “Economics Language and Assumptions: How Theories Can Become Self-Fulfilling.” The paper was written by professors Fabrizio Ferraro, of IESE Business School, Jeffery Pfeffer, of Stanford University, and Robert Sutton, of Stanford University. Stuart Bunderson was chair of the award committee. The rest of the committee consisted of Amy Edmondson, Henrich Greve, Glen Kreiner, Timothy Pollock, and Linn Van Dyne.